Diagnóstico molecular das infecções causadas pelos papilomavírus humanos no colo uterino - Carvalho, Maria Odete de Oliveira (2004)
Cervical cancer is the third major cause of death from cancer in female worldwide. From 2000, World Health Organization accepted a few types of genital Human Papillomavirus (HPV) as etiological agents of cervical cancer. Nevertheless, the diagnosis of such viral infections still needs improvements in order to contribute to cancer prevention. The objective of our study was to evaluate the use of molecular methodologies to access HPV DNA, in association to Cytopathology, the classical method of screening cervical lesions. The research was conducted by using samples from cervical smears of women attended at Laboratórios Dr Sérgio Franco, at Rio de Janeiro. They were analyzed by the Hybrid Capture Assay II (HCA II) and the Polymerase Chain Reaction (PCR) with generic primers MY 09/ MY 11. The study was composed by 1055 patients aging from 15 to 70 years old. HPV was detected in 48.3% of the smears, by HCA II, with a prevalence of 45.8% in patients aging from 20 to 30 years old. We observed that 88.2% of the infected women showed oncogenic HPV types, pointing to a high prevalence of patients with a high risk of cancer. We also conducted a comparative analysis between HCA II and PCR, for 40 samples, with the objective to determine the sensibility and the specificity of HCA II. HPV was detected in 75% of the samples, by HCA II, while PCR showed HPV in 70% of the patients. Cytopathology was used as a reference method of screening the lesions. The three tests showed absolute agreement when Cytopathology referred the sample as NORMAL. Disagreements occurred when Cytopathology pointed low squamous intraepithelial lesions (LSIL), in which HCA II showed 100% of HPV detection and PCR pointed only 85% of DNA detection. After comparing the two molecular techniques with Cytopathology results, we observed that in HCA II (p=0) as well as in PCR (p=0.002) a positive association was demonstrated. Hence, we concluded that, despite a few disagreements, HCA II showed to be sensitive and specific enough to be used in combination with cytopathology, especially in order to confirm ASCUS diagnosis and the presence of LSIL that shows persistence or reccurrence. Besides that, the evaluation of viral load measures obtained by HCA II showed to be related to the severity of the lesion and merits further studies to analyze possible association to risk of progression to malignancy.